KAJIAN ESTETIKA PADA FASAD BANGUNAN STASIUN (Studi Kasus : Stasiun Bogor) - Mahfud, Bay; Rahayu, Tuntun (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2022)
train station is a train operating facility or a place where trains stop regularly to pick up and drop off passengers or load and unload goods. Aesthetics comes from the Greek, aisthetica and aisthesis. Aesthetica are things that can be perceived or absorbed by the five senses, while aisthesis is sensory absorption or sensory perception. The facade or front of the building is the part that separates the outside and inside areas of the building, and serves as a differentiator between buildings that have the same function or not. In this study, the method used is descriptive qualitative method. the writer who becomes an instrument in research and analysis is carried out continuously from the beginning of the research to data analysis. In this research, it can be concluded that the Bogor Station Building applies forming elements to the facade including the entrance gate, ground floor zone, windows and entrances, guardrails, roofs and ornaments on the building and have facade aesthetic values by considering the layout, geometry, proportion, symmetry, rhythm (rhythm) and scale so as to produce a facade that has a 'feel'.